The clinical course of SARS-CoV-2 infection in patients with glomerular diseases and evaluation of the subsequent risk of relapse - Lionaki, Sophia; Dounousi, Evangelia; Marinaki, Smaragdi; Kantartzi, Konstantia; Papasotiriou, Marios; Galitsiou, Dimitra; Bellos, Ioannis; Sardeli, Aggeliki; Kalogeropoulos, Petros; Liakopoulos, Vassilios; Mpintas, Christos; Goumenos, Dimitrios; et al. (Frontiers in Nephrology, 2024)
IntroductionThis study aimed to describe the clinical course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with glomerular diseases (GDs) and its impact on the probability of relapse.MethodsPatients with biopsy-proven GD and positive PCR test for SARS-CoV-2 from glomerular clinics across Greece were studied retrospectively. Those who received the GD diagnosis after the SARS-CoV-2 vaccination or coronavirus disease 2019 (COVID-19) or ended in ESKD prior to infection were excluded. Demographics, histopathological diagnoses, past medical history, immunosuppression, and GD activity status were recorded.ResultsA total of 219 patients with GDs and documented SARS-CoV-2 infection were included. The mean time from the diagnostic kidney biopsy to SARS-CoV-2 infection was 67.6 ( ± 59.3) months. Among the participants, 82.5% had been vaccinated against SARS-CoV-2 with three doses (range: 2.5–3) without subsequent GD reactivation in 96.2% of them. Twenty-two patients (10%) were hospitalized for COVID-19 and one (0.5%) required mechanical ventilation. Four (1.8%) died due to COVID-19 and one (0.5%) had long COVID-19 symptoms. Among patients in remission prior to SARS-CoV-2 infection, 22 (11.2%) experienced a GD relapse within 2.2 (range: 1.5–3.7) months from the diagnostic test. The relapse-free survival after COVID-19 was significantly shorter for patients with minimal change disease, pauci-immune glomerulonephritis, and focal segmental glomerulosclerosis. No difference was observed in the relapse-free survival post-COVID-19 based on the history of SARS-CoV-2 vaccination.ConclusionsSARS-CoV-2 infection appears to have a symptomatic but uncomplicated sequence in vaccinated patients with GDs, with a significant impact on the clinical course of GD, associated with an increased probability of relapse in certain histopathological types.